2017
DOI: 10.1245/s10434-017-5875-6
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Low Preoperative Skeletal Muscle Mass in Patients Undergoing Gastrectomy for Gastric Cancer

Abstract: Preoperative SMI, measured in cross-section using CT, is a useful nutritional determinant that may predict OS and CSS in patients with GC who undergo gastrectomy. In our view, nutritional support for sarcopenic patients with stage I GC, aimed at retaining or adding skeletal muscle mass, may improve survival. Our analysis showed no relationship between preoperative SMI and postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 20 publications
2
86
1
1
Order By: Relevance
“…The association between low muscle mass and postoperative complications was reported in 12 studies [12,13,[23][24][25][26][27][28][29][30][31][32] of which 9 studies reported data on severe postoperative complications (Clavien-Dindo grade ≥III) [12,[23][24][25][26][27][28]31,32]. Overall mortality was reported as an outcome measure in 9 studies [24][25][26]28,31,[33][34][35], and 5 studies reported on disease-specific mortality [28,31,[33][34][35].…”
Section: Study Selectionmentioning
confidence: 99%
“…The association between low muscle mass and postoperative complications was reported in 12 studies [12,13,[23][24][25][26][27][28][29][30][31][32] of which 9 studies reported data on severe postoperative complications (Clavien-Dindo grade ≥III) [12,[23][24][25][26][27][28]31,32]. Overall mortality was reported as an outcome measure in 9 studies [24][25][26]28,31,[33][34][35], and 5 studies reported on disease-specific mortality [28,31,[33][34][35].…”
Section: Study Selectionmentioning
confidence: 99%
“…Generally, most studies reported an increased risk of postoperative morbidity with ORs of 3 to 9 27,28. However, such observations were not uniform, with some studies showing no effects on postoperative outcomes13,29,30 or impaired recovery only for subgroups i.e. severe sarcopenia 28 or sarcopenic obesity.…”
mentioning
confidence: 99%
“…The skeletal muscle mass was normalized by height in meters squared as the skeletal muscle index (SMI, cm 2 /m 2 ). Using the volume analyzer SYNAPSE VINCENT (Fujifilm, Tokyo, Japan), differential tissue areas were calculated in Hounsfield units (HU) . The skeletal muscle mass was evaluated within an HU range of −20 to 100 HU that was modified in a previous report to exclude vasculature and areas of fatty infiltration .…”
Section: Methodsmentioning
confidence: 99%
“…Using the volume analyzer SYNAPSE VINCENT (Fujifilm, Tokyo, Japan), differential tissue areas were calculated in Hounsfield units (HU). 22 The skeletal muscle mass was evaluated within an HU range of −20 to 100 HU 23 that was modified in a previous report to exclude vasculature and areas of fatty infiltration. 24,25 The VFA and SFA were calculated within an HU range of −200 to −50 HU.…”
Section: Methodsmentioning
confidence: 99%